Challenges and Possibilities of Deep Eutectic Solvent-Based Membranes - Zuniga-Navarro, G; Romero-Figueroa, J; Quijada-Maldonado, E; Araya-Lopez, C; Olea-Chandia, F (American Chemical Society, 2022)
Deep eutectic solvents (DES) are a category of a new class of solvents that can overcome some of the main drawbacks of typical solvents and ionic liquids (ILs). DES have been widely investigated and applied by the research community in several applications since their invention. Over the past years, the use of DES has been directed to the production of new materials and items for new products and processes. This is the case for the implementation of DES in various fields of chemical engineering directed to separations. DES have been very recently initiated to be combined into membranes for membrane processes. In this regard, this Review timely elucidates the current progress in utilizing this new generation of solvents in membrane preparation. In this work, different techniques, methods, and strategies for incorporating DES into polymer membranes for different concepts of membranes according to the final application have been reviewed. Particular emphasis has been devoted to the most relevant development works and results. After the current literature was analyzed, the main challenges and possibilities of DES in membranes were declared. © 2022 American Chemical Society.